Twins or the omega phase: Which is it in high carbon steels?. (September 2020) - Casillas, Gilberto; Song, Wenwen; Gazder, Azdiar A.
Abstract: Electron diffraction coupled with aberration-corrected (AC) scanning transmission electron microscopy (STEM) is used to image, identify and confirm the structure producing double diffracted spots seen in electron diffraction patterns in twinned high-carbon steels. The experimental and simulated data show that regions comprising: (i) overlaps between a twin and the matrix or, (ii) overlapping twins, create projected structures that are similar to the ω phase observed in other metastable bcc systems. Thus, AC STEM is proficient in the definitive identification of twins in bcc high carbon steels or nanoscale phases in metastable bcc systems. Graphical Abstract: Electron diffraction coupled with aberration-corrected STEM is used to image, identify and confirm the structure producing double diffracted spots seen in electron diffraction patterns in twinned high-carbon steels. Blue = matrix; Red = twin Image, graphical abstract